In Search of a Rainbow - Fynn- Thompson Ida (Literamed publications, 2011)
In an age of socio-economic challenges, two childhood friends - Bediako and Kobby swarm among the unemployed in their hometown. While the former strives in a boundless hunt to secure a job, the latter travels abroad in search of greener pastures. Find out how the decisions of these two young men transform their destinies.
Keywords: Juvenile Fiction / Realistic / Childhood Friendship